2014
DOI: 10.46743/2160-3715/2014.1032
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Research in Sport Management: Case Study as a Methodological Approach

Abstract: This paper presents qualitative research in sport management and suggests that case study is an appropriate qualitative methodology for research and practice in sport finance. The purpose of qualitative methodology is presented along with the process of a case study. The intention of this paper, for academicians working in sport management, is twofold. The first aspect is for researchers to consider using qualitative case study methodology in instances where such practice will progress the knowledge and unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…In conclusion, the results from this study fall in line with the previous research relating to the importance of collaborative action research in the field of sport management (Morse and McEvoy, 2014;Stringer, 2007). Brustad (2009) states, sport management's…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In conclusion, the results from this study fall in line with the previous research relating to the importance of collaborative action research in the field of sport management (Morse and McEvoy, 2014;Stringer, 2007). Brustad (2009) states, sport management's…”
Section: Discussionsupporting
confidence: 91%
“…The academic field of sport management has always thrived on its ability to create authentic learning experiences and produce professionals who are devoted to interdependent relationships between the community and various sporting organizations (Hoye et al, 2015). As a result of authenticity inherently built in to the world of sports management, it becomes imperative that research in the field revolves around action, participation, and human interaction (Morse and McEvoy, 2014). Specifically, sport management's "subject matter is comprised of human processes and experiences that are reflected in thoughts, emotions, and purposeful behaviors which are shaped by the dynamic flux of social life" (Brustad, 2009, p. 112).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the scarcity of research on this topic, qualitative research via case study methodology was used to understand social partnerships adequately (Yin, 2014). This study mostly followed the case study framework suggested by Morse and McEvoy (2014) and Misener and Doherty (2009) who identified best practice in case study methods in sports management research. From a sampling perspective, the partnerships were purposefully selected due to size variability, social cause engagement and relationship length.…”
Section: Methodsmentioning
confidence: 99%
“…A case study approach was selected for this study as the limited work on social partnerships in sport meant a more exploratory approach was needed to understand this phenomenon (Morse and McEvoy, 2014). Furthermore, comprehending the motives and implementation of social partnerships in professional sports required detailed information from those involved in the process.…”
Section: Introductionmentioning
confidence: 99%